2021
DOI: 10.1111/mec.15844
|View full text |Cite
|
Sign up to set email alerts
|

An inconvenient tooth: Evaluating female choice in multiple paternity using an evolutionarily and ecologically important vertebrate clade

Abstract: Understanding mating systems is a pillar of behavioural ecology, placing the complex interactions between females and males into a reproductive context. The field of multiple paternity, the phenomenon whereby many sires contribute to an individual litter, has traditionally viewed females as passive players in a male–male competitive framework. With the emergence of feminist perspectives in ecological fields, novel alternative mechanisms and evolutionary theories across invertebrate and vertebrate taxa recogniz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
1
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(31 citation statements)
references
References 128 publications
0
25
1
5
Order By: Relevance
“…Large females with large litters have a greater probability of their litters showing MP than those of small females, although both large and small females may engage in multiple matings. Some studies have attempted to assess the direct benefits that may be potentially enjoyed by females based on increased fecundity derived from polyandry (Lyons et al ., 2021; Pratt & Carrier, 2001); nonetheless, no significant differences have been found between the litter sizes of polyandrous and monandrous females of various shark species (Boomer et al ., 2013; Farrell et al ., 2014; Nosal et al ., 2013; Portnoy et al ., 2007; Veríssimo et al ., 2011). In Sphyrna tiburo from the western coast of Florida, large females tended to be polyandrous, although the limited number of polyandrous females in that study impeded any further conclusions on the matter (Chapman et al ., 2004).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Large females with large litters have a greater probability of their litters showing MP than those of small females, although both large and small females may engage in multiple matings. Some studies have attempted to assess the direct benefits that may be potentially enjoyed by females based on increased fecundity derived from polyandry (Lyons et al ., 2021; Pratt & Carrier, 2001); nonetheless, no significant differences have been found between the litter sizes of polyandrous and monandrous females of various shark species (Boomer et al ., 2013; Farrell et al ., 2014; Nosal et al ., 2013; Portnoy et al ., 2007; Veríssimo et al ., 2011). In Sphyrna tiburo from the western coast of Florida, large females tended to be polyandrous, although the limited number of polyandrous females in that study impeded any further conclusions on the matter (Chapman et al ., 2004).…”
Section: Discussionmentioning
confidence: 99%
“…M. henlei populations from the northeastern Pacific presented sireship skew. In Santa Catalina Island, three of the four litters with MP (75%; Chabot & Haggin, 2014) showed a marked sireship skew (Skew = 0.125 ± 0.138; Lyons et al ., 2021), with an average of 1.22 sires per litter. Similarly, in the northern Gulf of California, of the 13 litters with MP, 9 presented a clear sireship skew (70%; Skew = 0.086 ± 0.083; this study), with an average of 2.3 sires per litter.…”
Section: Discussionmentioning
confidence: 99%
“…MP has been an important topic for research in the Elasmobranchii, which includes sharks and rays (Lyons et al ., 2021). To date, MP is reported for 35 elasmobranchs (Lamarca et al ., 2020a); only three of them being rays (Batoidea), two myliobatiform species (Janse et al ., 2013; Lyons et al ., 2017) and one rajiform species (Chevolot et al ., 2007).…”
Section: Loci Pleo83 Pleo120 Pleo187mentioning
confidence: 99%
“…Convenience polyandry is when multiple mating occurs with females to avoid the physical costs of resisting copulation with different males and is widely used to explain MP in elasmobranchs (Daly‐Engel et al ., 2010). On the other hand, some evidence points to females having an active role in the reproductive system selection rather than being passive, due to potential benefits obtained from multiple mating (Lyons et al, 2021). Despite the different perspectives in female choice role, these concepts are not mutually exclusive and can occur simultaneously during a lifespan.…”
Section: Loci Pleo83 Pleo120 Pleo187mentioning
confidence: 99%
“…Multiple paternity (several sires contribute to an individual litter) is common in Elasmobranchs. Lyons et al (2021) examined this phenomenon from the perspective of the females, in an evolutionary context, and concluded that females are active stakeholders in the reproductive process. Zytynska et al (2021) presented the results from a meta‐analysis study to understand the generality of the costs and benefits of hosting facultative symbionts in plant‐sucking insects. Many animals have evolved associations with symbiotic microbes that benefit the host through increased growth, lifespan, and survival.…”
Section: Highlights Of 2021mentioning
confidence: 99%